MANAGING SUCCESSION IN A FAMILY OWNED SMALL-MEDIUM ENTERPRISES - Honey Nandlal; Suresh Kumar (International Journal of Family Business Practices, 2020)
Nowadays, family businesses are of high number in countires and contribute to the development of the economy. This research was conducted due to the importance of family business survival and it focuses on factors that affect their performance. Recently, family businesses have been identified as one of the concerns in the global entrepreneurial development agenda. This is because of the existing problem which is caused by family business owners avoid planning and treat succession as a problem instead of an opportunity. This impacts the continuity of the family-owned business. This research is made to emphasize the importance of planning and the drawbacks of negative bias in viewing succession as a problem. This study is expected to make family business owners understand the importance of planning and treating succession as an opportunity to achieve continuity. Qualitative research method was chosen as the method of the research with first generation family business owners as the key informants. Three key informants are chosen; Mr. Untoro A. Suryadi, Mr. IS and Mr. AS. In conclusion, family business should stop strategizing succession and treat succession as a practice.